A practical guide to suspected cervical spine injury. Issue 11 (November 2018) - Johnson, Graham
Abstract: Cervical spine injury is fortunately a rare entity in the paediatric population. Their assessment can be difficult and prove problematic for those unfamiliar with their assessment. We have provided a suggested approach in this article, with some discussion of the injuries that may be encountered.